2011
DOI: 10.1267/ahc.10039
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Immunocytochemical Localization of Amylase in Rat Parotid Glands and von Ebner's Glands by Ion Etching-Immunoscanning Electron Microscopy

Abstract: The distribution of amylase in rat parotid glands and von Ebner’s glands was examined using ion etching-immunoscanning electron microscopy, which enables both light and electron microscopic observations of identical semi-thin resin sections immunolabeled with anti-α-amylase and immunogold in association with silver enhancement. At the light microscopic level, most acinar secretory granules (SG) and striated duct secretions of parotid glands were strongly stained dark brown. In von Ebner’s glands, acinar SG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Saliva secretion is regulated by both sympathetic and parasympathetic nerve effects [ 40 ]. Hence, some short-term regulatory mechanisms for AQP5 and/or paracellular permeability have been predicted to be involved in the regulation of saliva secretion.…”
Section: Short-term Regulation Of Aqp5mentioning
confidence: 99%
“…Saliva secretion is regulated by both sympathetic and parasympathetic nerve effects [ 40 ]. Hence, some short-term regulatory mechanisms for AQP5 and/or paracellular permeability have been predicted to be involved in the regulation of saliva secretion.…”
Section: Short-term Regulation Of Aqp5mentioning
confidence: 99%
“…This study has demonstrated the existence of gustducin-immunoreactive cells as a constituent of the end portion of von Ebner’s glands in guinea pigs. Light and electron microscopic investigations have been performed in these glands for several mammalian species, except for the guinea pig (Hand 1970 ; Takeda 1976 ; Toyoshima and Tandler 1986 ; Azzali et al 1989 ; Gargiulo et al 1995 ; Cheng et al 2009 ; Isola et al 2010 ; Yahiro et al 2011 ). However, such non-granulated cells have not been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Parotid amylase plays a significant role in digesting polysaccharides. It is supposed to suppress adhesion to the vestibule surface and teeth [41]. Saliva is also rich in fluids and ions important for oral health.…”
Section: Introductionmentioning
confidence: 99%